Analisis Alih Kode dan Campur Kode Novel Jangan Pergi Lara Karya Mira W - Addiny Nur Azizah; Ita Kurnia; Elsiana Rahmawati; Putri Yessa Rahmawati (Institut Nalanda, 2024)
The aim of this research is to analyze the forms of code switching and code mixing in the novel